Female genital mutilation/cutting : global zero tolerance policy and diverse responses from African and Asian local communities - Nakamura, Kyoko; Miyachi, Kaori; Miyawaki, Yukio; Toda, Makiko (Springer, 2023)
This book shows how the adoption of global justice, such as eradication of female genital mutilation/cutting (FGM/C), has given rise to controversy, resistance, and transformation at the national, regional, and grass-roots levels in African and Asian countries where FGM/C has been practiced. It provides readers with up-to-date information about the effects of the campaign to eradicate FGM/C and the present situation of those countries, to which preceding books on FGM/C have scarcely referred. Adopting "zero tolerance" as a policy of eradication, WHO and other UN agencies have opposed any type of FGM/C, and many African countries have criminalized the practice. Although the campaign is based on the human rights discourse which is shared globally, the controversies concerning eradication of FGM/C on the national level and the responses of communities on the local level in those countries are diverse and complicated. Various actors such as NGOs, government officials, religious leaders, medical workers, and local inhabitants are embroiled and negotiate with each other concerning its eradication. With this book, readers are provided with an in-depth analysis of the complicated controversies and responses of local communities, referring to their particular historical and social backgrounds. The book provides two chapters on FGM/C in Asian countries, where not many studies have done yet. It also presents readers with a study of the arguments and responses to FGM/C of African immigrants by Australian health-care professionals as well as a study of male circumcision eradication campaigns, which have been carried on in tandem with FGM/C eradication campaigns but still not have been successful. With its many elaborate case studies, this book is highly recommended to readers who seek an in-depth and up-to-date integrated overview of the FGM/C studies as well as studies on the applicability of global justice to local communities. This is an open access book.